A Bronx tale broadband TV concern hooks up the 'hood. - Jones, W.D.
This paper describes how Urban Communications Transport has been making a profit in the telecommunication sector by providing cable television, broadband Internet access, and Internet telephony to residents in South Bronx, New York. Operating under the business name Urban Telephone and Video, the company caters to the diverse tastes of its subscribers who can get about 300 television channels, downstream data rates of up to 8 megabits per second, and Internet telephony with unlimited calling plans. These all-digital services come in on the same twisted copper pairs that once provided only plain old telephone service. Despite having to compete against network giants such as Time Warner and Cablevision, the company has found a way to get 10 to 15 percent of the market.
Keywords: Internet telephony; All digital services; Broadband Internet access; Broadband TV; Cable TV; Telecom industry; Urban communications transport; Urban telephone; Video-data.